2017
DOI: 10.1093/jjco/hyx093
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of definitive radiotherapy for neck node metastasis from unknown primary tumor: Japanese Radiation Oncology Study Group study

Abstract: Objective: To investigate the optimal treatment method and risk factor of neck node metastasis from unknown primary tumors (NUP) treated by radiotherapy. Methods: Retrospective case study based on a multi-institutional survey was conducted by the Japanese Radiation Oncology Study Group. Patients pathologically diagnosed as having NUP from 1998 to 2007 were identified. Univariate and multivariate analyses of overall survival (OS), progression free survival (PFS), neck progression free survival (NPFS) and mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(51 reference statements)
1
0
0
5
Order By: Relevance
“…They conclude that patients with N1 cancer without extracapsular extension (ECE) can be managed by surgery alone, whereas those with advanced disease and/or ECE are candidates for postoperative adjuvant radiation therapy. These findings are supported by a study by Yamazaki [ 25 ], which has reported negative ECE status is a factor associated with favorable OS and PFS. ECE is an unfavorable prognostic factor of neck recurrence, cause-specific survival, and overall survival.…”
Section: Discussionsupporting
confidence: 83%
“…They conclude that patients with N1 cancer without extracapsular extension (ECE) can be managed by surgery alone, whereas those with advanced disease and/or ECE are candidates for postoperative adjuvant radiation therapy. These findings are supported by a study by Yamazaki [ 25 ], which has reported negative ECE status is a factor associated with favorable OS and PFS. ECE is an unfavorable prognostic factor of neck recurrence, cause-specific survival, and overall survival.…”
Section: Discussionsupporting
confidence: 83%
“…Al momento de definir el tratamiento para nuestros pacientes, es necesario tener en cuenta los principales factores pronósticos en la MCCPD. Dentro de los factores significativos para tener una mejor sobrevida global y una supervivencia sin recurrencias son la ausencia de diseminación extracapsular, el estado de resección (R0 versus R1/R2), el nivel de ganglios linfáticos comprometidos en el cuello (I-III versus IV-V) y una mayor puntuación en el índice de Karnofsky 2,6,11 .…”
Section: Tratamiento Del Paciente Con Mccpdunclassified
“…Enfermedad del cuello poco avanzada, como los casos de N1 y N2a sin extensión extracapsular (ECE) en el examen histopatológico, muchos estudios informaron un excelente control regional tanto con cirugía exclusiva como con RT exclusiva 4,11,13 . Una posible ventaja de la RT sobre la cirugía es que permite el tratamiento de sitios de la mucosa en riesgo con una dosis subclínica de radiación 4 .…”
Section: Tratamiento De Modalidad úNicaunclassified
See 2 more Smart Citations